A pragmatic approach to estimating nondiscriminatory non‐tariff trade costs. Issue 4 (26th February 2022) - Herman, Peter R.
Abstract: Methods for estimating nondiscriminatory trade costs exhibit challenges in terms of data requirements or the ability to isolate the effects of specific policies. I propose a two‐stage approach that mitigates these limitations. It uses a structural gravity model to first estimate country‐level measures of aggregate nondiscriminatory trade costs. It then econometrically decomposes the aggregate costs into specific costs associated with policies while controlling for non‐cost factors that erroneously contribute to the aggregate estimates. Using the approach, I estimate specific costs for common non‐tariff measures and find they can represent significant barriers to trade, equivalent to a 0.9% tariff per measure.